Monitoring of crop growth parameters using temporal sar and optical remote sensing data in the Karasai district, Almaty region (Journal of Geography and Environmental Management, 2023)
Using Remote sensing data is essential in monitoring agricultural crop phenology and food security. The availability of optical and SAR imagery can provide the best insights into understanding the behavior of temporal characteristics of phenological stages of multiple agricultural crops.  The study was carried out in the region situated in the Karasai district of Almaty region using the temporal Sentinel-1 data and Sentinel-2 optical data during the growth period of agricultural crops. NDVI values from the Sentinel-2 and Multitemporal VH/VV backscatter intensity from Sentinel-1 SAR with the sample data were used to characterize the backscatter and vegetation stage behavior of multiple crops. Crop growth parameters were calculated using Google Earth Engine platform. Google Earth Engine is a cloud-based platform that allows users to visualize and analyze satellite images of the Earth and make geospatial analysis. The results indicate that the phenological stages of the agricultural crop growth cycle may be recognized and distinguished based on the temporal variations of NDVI values and in SAR parameters that were detected. Also according to the result of the study it is visible that the trend charts of backscattering values are quite correlated with the NDVI value. NDVI with backscatter values of VV/VH can be considered as one of the beneficial tools for distinguishing and analyzing the phenological changes of different types of agricultural crops.
Keywords: Crop growth parameters, backscatter intensity parameters, NDVI, Sentinel-1, Sentinel-2